A seat at the table is not enough: understanding women's substantive representation in peace processes. (3rd May 2016) - Ellerby, Kara
Abstract: While the international community stresses the importance of including women at the peace table so peace processes will better represent their needs and interests, it is unclear what specifically this inclusion entails. Do women need to be negotiators, mediators? Do peace agreements adequately represent women's interests when women are included? This article engages UNSC Resolution 1325 on Women, Peace and Security as a framework through which to assess peace processes and agreements. A woman-focused examination of all civil war peace processes reveals that less than 10% meet women's inclusion as envisioned in UNSCR 1325. This article focuses on the three conditions accounting for women's substantive representation in peacebuilding. What emerges are three joint necessities: an explicit women's agenda ; access to the peace process; and advocacy within the process. The final sections problematise how even in all of these positive cases women had to fight to participate.